Understanding knowledge needs for Scotland to become a resilient Hydro Nation: Water stakeholder perspectives. Issue 136 (October 2022) - Adams, Kerr J.; Metzger, Marc J.; Macleod, Christopher (Kit) J.A.; Helliwell, Rachel C.; Pohle, Ina
Abstract: Freshwater resources provide ecosystem services that support human prosperity and development. Future changes in climate, land-use, and population could lead to detrimental impacts on freshwater quality and quantity, threatening drinking water, irrigation and energy production. To increase resilience there is the need to better understand the possible impacts of future changes on freshwaters. We use Scotland – and its legislative agenda 'Scotland: The Hydro Nation' – to understand the knowledge needs of water stakeholders as a first step in building freshwater resilience. By interviewing water stakeholders across Scotland, we found an overarching 'knowledge need' for a greater understanding of the cumulative impacts on freshwaters associated with the interactions between multiple climatic and socio-economic drivers and their associated pressures. Stakeholders also identified five specific 'knowledge need' themes; large-scale land-use change, future water demands, water value, integrated development planning and water asset conditions. We identify a willingness of stakeholders to participate in systems-thinking approaches to address these 'knowledge need' themes. The 'knowledge needs' can be used to inform research priorities to support water-related policy in Scotland. We propose that participatory methods should be applied following the Driver Pressure State Impact Response (DPSIR) framework to address 'knowledge need themes' to identify and appraise adaptive management and policy options. Our methods used to identify stakeholder knowledge needs are a time, cost and environmentally effective way for collecting rich data. Methods can be replicated in other regions and water policy contexts to understand where increased knowledge is required to help build future resilience. Highlights: Stakeholder 'knowledge need' findings can be used to inform research priorities and water related policy. Identified stakeholder desire for improved holistic systems-thinking approaches to address identified 'knowledge needs'. Participatory approaches can be applied to support the identification of adaptive management and policy options. Methods to elicit stakeholder 'knowledge needs' can be replicated as a first step in building resilient water policy.